TRAVELLING WAVE PHENOMENON IN OPTICAL CAVITIES MODEL - Irianto, Jonathan
The optical cavities model is an optical resonator that forms a standing wave in the resonator cavity for light waves. The optical cavities model used is a one-dimensional lattice equation which models the light field in an optical system comprised of a periodic array of optical cavities pumped by a coherent light source. When the optical cavities model is fired by light in an area that does not have an equilibrium solution, it turns out that the light will move to an area that has an equilibrium solution. This phenomenon is called the traveling wave phenomenon where there is a transfer of light from an area that does not have an equilibrium solution to an area that has an equilibrium solution. In this study, the author will look for the existence of the traveling wave phenomenon that occurs in the optical cavities model using several different parameters and look for the speed of the traveling wave phenomenon that occurs.